Evidence for magnesium–phosphorus synergism and co-limitation of grain yield in wheat agriculture - Martin Weih (Nature Portfolio, 2021)
Abstract Modern crop production is characterized by high nitrogen (N) application rates, which can influence the co-limitation of harvested yield by other nutrients. Using a multidimensional niche volume concept and scaling exponents frequently applied in plant ecological research, we report that increased N and phosphorus (P) uptake in a growing wheat crop along with enhanced grain biomass is associated with more than proportional increase of other nutrients. Furthermore, N conversion efficiency and grain yield are strongly affected by the magnesium (Mg) to P ratio in the growing crop. We analyzed a field trial in Central Sweden including nine wheat varieties grown during two years with contrasting weather, and found evidence for Mg co-limitation at lower grain yields and P co-limitation at higher yields. We argue that critical concentrations of single nutrients, which are often applied in agronomy, should be replaced by nutrient ratios. In addition, links between plant P and Mg contents and root traits were found; high root number enhanced the P:N ratio, whilst steep root angle, indicating deep roots, increased the Mg:N ratio. The results have significant implications on the management and breeding targets of agriculturally grown wheat, which is one of the most important food crops worldwide.